Two Distinct Yersinia pestis Populations Causing Plague among Humans in the West Nile Region of Uganda - Respicio-Kingry, Laurel B. (PLoS Negl Trop Dis, 2016)
BACKGROUND: Plague is a life-threatening disease caused by the bacterium, Yersinia pestis. Since the 1990s, Africa has accounted for the majority of reported human cases. In Uganda, plague cases occur in the West Nile region, near the border with Democratic Republic of Congo. Despite the ongoing risk of contracting plague in this region, little is known about Y. pestis genotypes causing human disease. METHODOLOGY/PRINCIPAL FINDINGS: During January 2004–December 2012, 1,092 suspect human plague cases were recorded in the West Nile region of Uganda. Sixty-one cases were culture-confirmed. Recovered Y. pestis isolates were analyzed using three typing methods, single nucleotide polymorphisms (SNPs), pulsed field gel electrophoresis (PFGE), and multiple variable number of tandem repeat analysis (MLVA) and subpopulations analyzed in the context of associated geographic, temporal, and clinical data for source patients. All three methods separated the 61 isolates into two distinct 1.ANT lineages, which persisted throughout the 9 year period and were associated with differences in elevation and geographic distribution. CONCLUSIONS/SIGNIFICANCE: We demonstrate that human cases of plague in the West Nile region of Uganda are caused by two distinct 1.ANT genetic subpopulations. Notably, all three typing methods used, SNPs, PFGE, and MLVA, identified the two genetic subpopulations, despite recognizing different mutation types in the Y. pestis genome. The geographic and elevation differences between the two subpopulations is suggestive of their maintenance in highly localized enzootic cycles, potentially with differing vector-host community composition. This improved understanding of Y. pestis subpopulations in the West Nile region will be useful for identifying ecologic and environmental factors associated with elevated plague risk.